(untitled) (REDEL. Revista Granmense de Desarrollo Local, 2021)
Local development remains a priority to the Cuban government. That is why the scientific production increases in order to find new ways to strengthen the governements´ steps at that level. This research falls within the studies carried out with that goal in Cuba. It hold as a general objective to devise a methodology to contribute to the diagnosis of cultural potentialities for the development of “La Demajagua” People´s Council. In order to fulfill such a goal, there were determined the theoretical foundations sustaining the research, and there were analyzed the documents and instructions for diagnosing within the people´s council as well as the practice developed by the community work groups of the different districts. That revealed the inexistence of a methodology to diagnose the cultural potentialities of the locality. In the report, the subject dealt with is supported taking into account criteria from different authors. Likewise it presents the methodology devised with precise guidelines for its application. That makes up the practical contribution of this study, which has been endorsed by its benefitiaries.